A more physiological approach to lipid metabolism alterations in cancer: CRC-like organoids assessment - Cruz-Gil, Silvia; Schölch, Sebastian (PLOS ONE, 2019)
Precision medicine might be the response to the recent questioning of the use of metformin as an anticancer drug in colorectal cancer (CRC). Thus, in order to establish properly its benefits, metformin application needs to be assayed on the different progression stages of CRC. In this way, intestinal organoids imply a more physiological tool, representing a new therapeutic opportunity for CRC personalized treatment to assay tumor stage-dependent drugs. The previously reported lipid metabolism-related axis, Acyl-CoA synthetases/ Stearoyl-CoA desaturase (ACSLs/SCD), stimulates colon cancer progression and metformin is able to rescue the invasive and migratory phenotype conferred to cancer cells upon this axis overexpression. Therefore, we checked ACSL/SCD axis status, its regulatory miRNAs and the effect of metformin treatment in intestinal organoids with the most common acquired mutations in a sporadic CRC (CRC-like organoids) as a model for specific and personalized treatment. Despite ACSL4 expression is upregulated progressively in CRC-like organoids, metformin is able to downregulate its expression, especially in the first two stages (I, II). Besides, organoids are clearly more sensitive in the first stage (Apc mutated) to metformin than current chemotherapeutic drugs such as fluorouracil (5-FU). Metformin performs an independent “Warburg effect” blockade to cancer progression and is able to reduce crypt stem cell markers expression such as LGR5+. These results suggest a putative increased efficiency of the use of metformin in early stages of CRC than in advanced disease.